Comparing Standard Keratometry and Total Keratometry Before and After Myopic Corneal Refractive Surgery With a Swept-Source OCT Biometer - Wang, Ziyang; Song, Yanzheng; Yang, Wenli; Li, Dongjun; Chen, Wei; Zhao, Qi; Liu, Qian; Zhai, Changbin (Frontiers in Medicine, 2022)
Background More recently, the swept-source OCT biometer-IOLMaster 700 has provided direct total corneal power measurement, named total keratometry. This study aims to evaluate whether standard keratometry (SK) and total keratometry (TK) with IOLMaster 700 can accurately reflect the corneal power changes induced by myopic corneal refractive surgery. Methods In this study, the biometric data measured with the swept-source OCT biometer—IOLMaster 700 before and 3 months after the myopic corneal refractive surgery were recorded. The changes of biological parameters, including SK, posterior keratometry (PK), and TK, and the difference between SK and TK were compared. In addition, the changes of SK and TK induced by the surgery were compared with the changes of spherical equivalent at the corneal plane (ΔSEco). Results A total of 74 eyes (74 patients) were included. The changes of SK, PK, TK, axial length, anterior chamber depth, and lens thickness after refractive surgery were all statistically significant (all p < 0.01), while the change of white-to-white was not (p = 0.075). The difference between SK and TK was −0.03 ± 0.10D before the corneal refractive surgery and increased to −0.78 ± 0.26D after surgery. The changes of SK and the changes of TK induced by the surgery had a good correlation with the changes of SEco (r = 0.97). ΔSK was significantly smaller than ΔSEco, with a difference of −0.65 ± 0.54D (p < 0.01). However, the difference between ΔTK and ΔSEco (0.10 ± 0.50D) was not statistically significant (p = 0.08). Conclusions Using SK to reflect the changes induced by the myopic corneal refractive surgery may lead to underestimation, while TK could generate a more accurate result. The new parameter, TK, provided by the IOLMaster 700, appeared to provide an accurate, objective measure of corneal power that closely tracked the refractive change in corneal refractive surgery.